2009
DOI: 10.1021/ja906773g
|View full text |Cite
|
Sign up to set email alerts
|

Seeded Growth of CdS Nanoparticles within a Conducting Metallopolymer Matrix

Abstract: Electropolymerization of bithiophene-substituted cadmium(II) Schiff base complexes forms thin conducting metallopolymer films with metal centers distributed throughout. The metal centers act as seed points for direct growth of CdS nanoparticles within the polymer matrix under mild reaction conditions. This synthetic approach offers control over both the size and distribution density of the nanoparticles formed within the polymer film. The resulting hybrid materials hold promise for a variety of organic electro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
36
0

Year Published

2010
2010
2014
2014

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 34 publications
(37 citation statements)
references
References 16 publications
1
36
0
Order By: Relevance
“…A further approach to prepare metal sulfide nanoparticles in a polymer matrix was reported by Mejía et al [132]. They For example, it will be especially exciting to follow if it will also be possible to synthesize nanorods in solid state reactions in conjugated polymer matrices.…”
Section: Examples Of Further Ligand-free Methods For the Preparation mentioning
confidence: 99%
“…A further approach to prepare metal sulfide nanoparticles in a polymer matrix was reported by Mejía et al [132]. They For example, it will be especially exciting to follow if it will also be possible to synthesize nanorods in solid state reactions in conjugated polymer matrices.…”
Section: Examples Of Further Ligand-free Methods For the Preparation mentioning
confidence: 99%
“…The incorporation of these as metal centers in conducting metallopolymers are important for a variety of applications including the seeded growth of semiconductor nanoparticles within a polymer matrix [8][9][10][11][12][13].…”
Section: Introductionmentioning
confidence: 99%
“…We have previously shown that metal Schiff base complexes with bithiophene end groups can be used as precursors for hybrid materials [8][9][10][11][12][13]. Upon electropolymerization, the monomers give a polymer film with metal seed points disbursed throughout.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This adsorbate was selected because of the possibility of spectrophotometric monitoring of the process, and also the potential possibility of its post-sorption conversion to copper(II) sulfide when treated with sulfide ions. The fruitfulness of such an approach was demonstrated recently when a composite material was obtained based on conductive organic polymers and cadmium sulfide nanoparticles [12].…”
mentioning
confidence: 99%